2018
DOI: 10.2147/opth.s172400
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the filtration-bleb volume after Ex-PRESS<sup>&reg;</sup> surgery

Abstract: PurposeThe aim of this study was to investigate the factors influencing the volume of the filtration bleb after Ex-PRESS® surgery.MethodsThis was a retrospective non-randomized study. After excluding patients who had undergone an additional glaucoma surgery, 99 glaucoma patients who underwent Ex-PRESS® surgeries and were followed up for >2 years were analyzed. We used anterior segment optical coherence tomography to measure the bleb volume, and compared the volume at 1 year with that at 2 years after surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…In the current study, the bleb volume decreased in the XFG group compared with the POAG group 6 months after Ex-PRESS surgery. Our results agreed with a previous report by Tojo et al 18 at 1 year after Ex-PRESS surgery. A more detailed evaluation showed that the fluid-filled space volume was smaller in the XFG group compared with the POAG group 3 and 6 months postoperatively ( Table 2 ).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In the current study, the bleb volume decreased in the XFG group compared with the POAG group 6 months after Ex-PRESS surgery. Our results agreed with a previous report by Tojo et al 18 at 1 year after Ex-PRESS surgery. A more detailed evaluation showed that the fluid-filled space volume was smaller in the XFG group compared with the POAG group 3 and 6 months postoperatively ( Table 2 ).…”
Section: Discussionsupporting
confidence: 94%
“…For example, we focused on POAG and XFG, performed Ex-PRESS surgery with a fornix-based conjunctival flap, and analyzed the morphology in a limited region of the bleb centered on the scleral flap up to 6 months postoperatively. In the study of Tojo et al, 18 the surgical procedure and glaucoma types were similar to those of the current study, but those authors evaluated patients 1 year or more postoperatively, and several patients had markedly high IOP. Narita et al 23 performed trabeculectomy with a fornix-based conjunctival flap for several glaucoma types and evaluated patients 1 year postoperatively.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Another recent study evaluating Japanese patients found that advanced age, higher postoperative IOP, pseudo-exfoliation glaucoma, and simultaneous cataract surgery negatively influence the volume of the filtration bleb 2 years after surgery [15]. It must be said that in the latest study, hemoglobin-A1C was not measured, and EX-PRESS represented the first-line surgical treatment, without previous or subsequent glaucoma surgeries; therefore, it is difficult to make direct comparisons between our study and the Japanese report.…”
Section: Failurementioning
confidence: 99%